Kesesuaian Ketinggian Tempat terhadap Penerapan Sistem Tanam Legowo untuk Peningkatan Produksi Padi - Agustiani, Nurwulan; Sujinah, Sujinah; Hikmah, Zaqia M. (Jurnal Penelitian Pertanian Tanaman Pangan, 2018)
This research was to obtain information of rice planting system technology based on altitude and type of varieties that correlated with high productivity. The experiment was conducted at dry season 2016 in three districts, Bandung, Subang, and Indramayu representing the high, mid and low altitudes. Experiment was arranged in split plot with 6 replications. The main plot was variety representing 2 type of variety, i.e (1) Inbred Inpari 32 and (2) Hybrid Hipa 18. The sub plot was planting system : (1) tegel (25x25 cm), (2) legowo 2:1 (25x12,5x50 cm), and (3) legowo 4:1 type 2 (25x12,5x50 cm). The result showed that growth and yield were very specific to pattern of planting system and type of variety. The interaction between location and planting system significantly to tiller number, leaf area, biomass, growth rate, and nett assimilation. In general, application of legowo planting system provided a higher yield than square planting system (tegel). In addition, increased production with application of legowo planting system suitable in upland for both Inpari 32 and Hipa 18. Otherwise, its application in midle and lowland not significant increased yield.